Management and Utilization of Nusa Penida Island by Foreign Nationals in Relation to Licensing Regulations in Indonesia - rosidah, zaidah nur; Liza Priandhini (Faculty of Law, Universitas Pekalongan, 2025)
This paper examines the management and utilization of small islands in Indonesia, specifically Nusa Penida, by foreign nationals(WNA) in relation to the prevailing legal regulations on land and investment permits. Indonesia, being an archipelagic nation, ishome to numerous islands that attract both local and foreign investors, especially in tourism. The legal framework governingforeign investment in small islands, including the necessary permits, is explored, with particular focus on the requirements set out inthe Indonesian legal system, such as the UUPA (Agrarian Law), the Management of Coastal Areas and Small Islands (PWP3K Law), andvarious ministerial regulations. The paper addresses how foreign nationals engage in island management in Nusa Penida,particularly in tourism-related ventures like hotels, resorts, and recreational activities such as diving and snorkeling. It evaluates theimpact of such foreign investments on the local community, highlighting both positive and negative aspects. One significant issuediscussed is the long-term land leasing agreements between foreign nationals and Indonesian landowners, which may potentiallylead to unintended ownership transfers andlegal disputes, as well as challenges in ensuring compliance with Indonesian land laws.The study also delves into the regulatory gaps in the implementation of these laws, particularly the lack of clear procedural guidelines for foreign investment in small islands. Furthermore, it calls for stricter enforcement and monitoring of land use and property transactions to prevent the unregulated acquisition of land by foreign nationals and to protect the national interest.Finally, the paper offers recommendations for improving legal oversight, such as ensuring proper registration of land transactions,enhancing the role of notaries and land officials in verifying the legality of land agreements, and ensuring that foreign investments arealigned with Indonesia's economic and environmental goals. The findings suggest that while foreign involvement in small islandmanagement can contribute to the local economy, stringent legal frameworks and thorough monitoring are essential to safeguardthe nation's sovereignty over its natural resources.